FUZZY-LOGIC-BASED ERGONOMIC ASSESSMENT IN AN AUTOMOTIVE INDUSTRY - Kamala, Vijayakumar; Paul Robert, T (The South African Journal of Industrial Engineering, 2022)
The objective of this study was to develop and evaluate a tool for measuring an organisation’s ergonomic level. The study was carried out to fill a research gap in which no attempt had been made to design an index for evaluating a company’s ergonomics. An ergonomic index measuring model with 15 criteria using a fuzzy logic technique was developed during this study. The fuzzy ergonomic index (FEI), which represents the ergonomic level of the company, and the fuzzy performance importance index, which assists in resolving ergonomics barriers, were then calculated. The findings show that the model is capable of analysing ergonomics adequately and has practical application. Application of the methodology presented in this paper will reveal the measures necessary to improve an organisation’s ergonomic level.